2010
DOI: 10.1016/j.scitotenv.2010.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Variations in vanadium, nickel and lanthanoid element concentrations in urban air

Abstract: The emission of trace metal pollutants by industry and transport takes place on a scale large enough to alter atmospheric chemistry and results in measurable differences between the urban background of inhalable particulate matter (PM) in different towns. This is particularly well demonstrated by the technogenic release into the atmosphere of V, Ni, and lanthanoid elements. We compare PM concentrations of these metals in large datasets from five industrial towns in Spain variously influenced by emissions from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
67
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(88 citation statements)
references
References 40 publications
13
67
0
1
Order By: Relevance
“…92). Studies in Spain (101) and in the United States (14,102) show similar findings. Based on estimates of the current mix of petroleum products exploited (described above), we estimate that unconventional fuels, with their higher V concentrations, represent about 40.5% (166 × 10 9 g V/y) of the total V mobilized to the atmosphere from the extraction of petroleum (410 × 10 9 g V/y).…”
Section: Sinks For V Mobilized From Earth's Crustsupporting
confidence: 52%
See 1 more Smart Citation
“…92). Studies in Spain (101) and in the United States (14,102) show similar findings. Based on estimates of the current mix of petroleum products exploited (described above), we estimate that unconventional fuels, with their higher V concentrations, represent about 40.5% (166 × 10 9 g V/y) of the total V mobilized to the atmosphere from the extraction of petroleum (410 × 10 9 g V/y).…”
Section: Sinks For V Mobilized From Earth's Crustsupporting
confidence: 52%
“…Our calculation of the sum of wet and dry deposition (72 × 10 9 g/y) is less than the estimated sources to the atmosphere, leaving us with an unbalanced budget for V in the atmosphere. In urban areas, airborne concentrations can exceed 10 × 10 −9 g/m 3 (14,92,101,102), so the atmospheric budget may be balanced by dry deposition near emission sources.…”
Section: Sinks Of V From the Atmospherementioning
confidence: 99%
“…The average value for V/Ni in UCC is around 2, with most sedimentary rocks, the finer fractions of soils, and ambient atmospheric PM exhibiting values confined within a range of 1-4 (Rudnick and Gao, 2004;Pey et al, 2009). Similarly, V/Ni values in low-sulphur petcoke and fuel oils typically lie a range of 1-3, increasing to 4-8 in high sulphur residues such as petcoke and the cheaper bunker oils used as fuel by shipping on the open seas where harbour controls on sulphurous emissions do not apply (Moreno et al, 2010;Pandolfi et al, 2011a). In the case of the MSY and BCN averaged data, all three PM size fractions show a range in V/Ni of 1-3, making unlikely any significant influence from high-sulphur shipping emissions (although individual hourly V/Ni ratios could exceed this value, due to the influence of industrial local emissions or the sporadic arrival of air masses contaminated by the use of less clean oils).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, V has, also in this case, the highest EF in SA. Vanadium is emitted from all sources using heavy fuel oils such as ship engines and power plants (Becagli et al, 2012;Moreno et al, 2010;Toscano et al, 2011): therefore, this result is probably due to the input of air from the sea, as SA is relatively close to an important harbour and to a great coal power station localised in Savona city (Liguria region). To evaluate this hypothesis we calculated back-trajectories Taking wind direction and atmospheric conditions data into account and running deposition simulations by NOAA Hysplit Dispersion Model (Draxler and Rolph, 2015) and found that, particularly during summer days, air masses arriving in SA originate mainly from sea.…”
Section: Pm10 Concentration and Chemical Compositionmentioning
confidence: 99%